Strategi Dinas Perdagangan, Perindustrian Dan Koperasi Dalam Meningkatkan Daya Saingproduk Lokal Di Sektor Usaha Kecil Menengah Di Kabupaten Soppeng - Putra, Ferdynzah; Muhammadiah, Muhammadiah; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2020)
This study purposed to determine the Cost Excellence Strategy, Differentiation Strategy and Focus Strategy of the Department of Trade, Industry and Cooperatives in Soppeng Regency. This study used qualitative descriptive with its type case study. Data collection techniques used interviews with informants as many as 9 people. The results of this study showed that in terms of cost advantage strategies required aggressive construction of efficient facilities and vigorous efforts to achieve cost reduction. This strategy emphasized how to increase organizational productivity by seeing costs as an important factor to achieve goals, then in terms of differentiation strategies it could be seen that the products produced by SMEs had been made as attractive as possible in terms of packaging. so that the product was able to compete and enter retail stores and had its own brand to make it easier for consumers to know the local products of Soppeng Regency, and the last was the focus strategy that was known that the marketing of local products was not only within the Soppeng Regency environment, but rather the marketing was also outside Soppeng Regency. This product marketing also usesd online media such as Instagram and other social media.